Multilevel governance of coastal flood risk reduction: A public finance perspective. Issue 112 (October 2020) - Bisaro, Alexander; de Bel, Mark; Hinkel, Jochen; Kok, Sien; Stojanovic, Tim; Ware, Daniel
Highlights: We compared multilevel coastal flood risk reduction governance and public finance in the UK, Germany, the Netherlands and Australia. We evaluated alignment of multilevel governance arrangements to spillovers from coastal risk reduction based on fiscal federalism. We find diverse coastal flood risk governance arrangements ranging from highly centralised to full decentralisation. We find that multilevel coastal flood risk governance arrangements are reflective of the distribution of the benefits across different levels of government. We find that major fiscal redistributions may be put under pressure by rising costs under SLR and coastal development. Abstract: Coastal flood risk reduction (CFRR) presents a significant public funding challenge, due to its high upfront costs and long-term benefits, and this challenge will increase with future sea-level rise. The funding challenge necessarily involves multiple levels of government, due to the regional nature of CFRR public goods involved. Yet there has been little research comparing such multilevel arrangements across countries, and in particular exploring the performance of public funding arrangements for providing coastal flood risk reduction. We address this gap, applying fiscal federalism to develop a multilevel governance analysis of public decision-making and fiscal authorities for CFRR in the Netherlands, Germany, the UK and Australia. For each country, we locate key decision-making and fiscal authorities in multilevel governance arrangements, and analyse their alignment with the benefits of CFRR measures (spillovers). We find diverse coastal flood risk governance arrangements ranging from highly centralised (NL), mixed arrangements, involving regional centralisation (Germany) or partial devolvement (UK), to full decentralisation (AUS). Further, we find that in accordance with fiscal federalism, multilevel coastal flood risk governance arrangements are generally reflective of the distribution of the benefits across different levels of government, with some exceptions (Germany and UK). Finally, exploring the outlook of current arrangements under sea-level rise, we find that major fiscal redistributions may be put under pressure by rising costs likely under SLR and future coastal development. This is particularly the case for those systems which operate under hazard-based, as opposed to risk-based, coastal protection policies. Further, we find that both fully and moderately decentralised arrangements may require greater central support for alternative measures, such as retreat, in light of growing financial burdens on local governments.